Oxidative Stress and Antioxidant Status in Vitiligo Patients - Haider, Naushin; Islam, Mohammad Safiqul; Al Maruf, Abdullah; Shohag, Md Hasanuzzaman; Ali, Rubaiya; Rahman, GKM Mustafizur; Hasnat, Abul (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Vitiligo is a common pigmentary disorder characterized by depigmented patches or macules caused by the destruction of melanocytes. The pathogenetic mechanisms involved in vitiligo have not been completely clarified. Oxidative stress and reduced circulating antioxidants could be important phenomena in the pathophysiology of vitiligo. We measured serum malondialdehyde (MDA) as an indicator of oxidative stress and serum zinc and vitamin C to check antioxidant status in thirty Vitiligo patients. Thirty healthy control subjects were also recruited by matching the socio-demographic status to that of the patients. Blood samples were analyzed for determining the serum levels of Zn (by atomic absorption spectroscopy), Vitamin C and MDA (by UV-VIS spectroscopy). Serum level of MDA increased in vitiligo patients significantly (p < 0.05) in the present study, where as serum level of Zn increased and serum Vit-C decreased in patients compared to control but the changes were not statistically significant (p > 0.05). Our study reveals the presence of an imbalance in the oxidant/antioxidant system in vitiligo patients which supports a free radical-mediated damage in the pathogenesis of vitiligo. Key words: Vitiligo; Oxidative stress; Antioxidant status; MDA; Vitamin C; Zinc DOI: http://dx.doi.org/10.3329/dujps.v9i2.7894 Dhaka Univ. J. Pharm. Sci. 9(2): 103-108, 2010 (December)